A Critical Mixed-Methods Analysis of Student-Teachers’ Action Research Challenges and Institutional Mediation in Ghanaian Colleges of Education - Benjamin Quarshie; Akwasi Amponsah; Henry Ofosu Ameyaw; Anthony Mensah; Mercy Anna Ayi-kooley Malm; Moses Jahkumah Appiah-Quansah (International Journal of Education and Teaching Zone, 2026)
Action research is a core component of Ghana’s Initial Teacher Education (ITE) framework, designed to foster reflective practice and inquiry-based problem-solving during student-teachers’ internships. However, ongoing difficulties in its implementation raise concerns about the adequacy of institutional and supervisory support. This study explores the lived experiences of final-year student-teachers conducting action research in Colleges of Education in Ghana. Using a mixed-methods embedded design, quantitative and qualitative data were collected from 240 student-teachers across 16 colleges. Descriptive statistics and thematic analysis identified key challenges, assessed institutional support structures, and examined coping strategies. Findings indicate major difficulties in problem identification, data analysis, and academic writing, intensified by irregular supervision, limited methodological guidance, logistical constraints, and cognitive-emotional pressures. Nevertheless, most participants reported improved reflective thinking and classroom problem-solving. The study proposes a conceptual framework linking student challenges with institutional support and recommends scaffolded research pedagogy, standardized supervision, and enhanced digital infrastructure to strengthen sustainable research capacity.